Drug interactions profile of Oral Antineoplastic Agents (OAAs) dispensed for oncologic patients (Research, Society and Development, 2020)
The present study aims to list the oral antineoplastic agents (OAAs) most dispensed in an oncology hospital, identifying their doses, indications, contraindications and possible drug interactions (DIs). Documentary, retrospective, analytical and descriptive study, where OAAs dispensation spreadsheets were analyzed, from january to july 2019. Data were obtained from Micromedex® and analyzed by SPSS® (version 20) using descriptive statistics. 22 types of OAAs were dispensed, making a total of 360.703 drugs. Anastrozole was the most prescribed (51,85%) and hormone therapy agents (32%) were considered the main group. Tyrosine kinase inhibitors exposed the highest rates of contraindications (n=64). With regard to serious risk interactions, nilotinib (n=264), dasatinib (n=182) and metotrexate (n=134) were the drugs with the highest number of reports. The OAAs that did not present any type of interaction were anastrozole and diethylstilbestrol. Of the pharmacological agents that most interacted with OAAs, live vaccines (n=11) were the most present in contraindications and warfarin was the one that had the highest rate of serious interactions (n=8). As for the repercussions of DIs, the most frequent indices were the increased risk of prolongation of the QT interval (n=67) and increased exposure to a drug (n=51). Bearing in mind that cancer therapy requires special attention because of the possible interactions with OAAs, these results are shown to be a useful tool for the entire multiprofessional health team, especially the pharmacist, who has an essential role in the pharmaceutical assistance service on an outpatient basis.